HUBUNGAN HEALTH BELIEF DAN HEALTH LITERACY DENGAN KEPATUHAN PENGOBATAN PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS KECAMATAN CIRACAS JAKARTA TIMUR - Nurul Aliyyah Rahmah, (2022)
The results of the 2018 Basic Health Research stated that the prevalence of hypertension in Indonesia had increased from the previous 25.8% in 2013 to 34.11% in 2018 this means that hypertension sufferers still have poor control levels which are manifested by as much as 32.3% Patients with hypertension do not routinely take medication and another 13.3% do not take medication. To effectively improve adherence, several factors such as perceptions of health beliefs and health literacy can be modified to improve medication adherence behavior in people with hypertension. This study aims to determine the relationship between health belief and health literacy with medication adherence in patients with hypertension in the Work Area of the Public Health Center, Ciracas District, East Jakarta. The research method used is descriptive analytic with cross sectional design. The data collection technique used was purposive sampling with a total sample of 108 respondents. The results showed that there was a relationship between health literacy and medication adherence (p value = 0.028) and there was a relationship between health belief and medication adherence (p value = 0.035). Health service providers are expected to improve health education interventions with hypertension sufferers, especially in hypertension patients with poor health belief and inadequate health literacy in order to increase better perceptions of medication adherence behavior.